2005
DOI: 10.1124/jpet.105.090365
|View full text |Cite
|
Sign up to set email alerts
|

Unequal Neuroprotection Afforded by the Acetylcholinesterase Inhibitors Galantamine, Donepezil, and Rivastigmine in SH-SY5Y Neuroblastoma Cells: Role of Nicotinic Receptors

Abstract: Donepezil, rivastigmine, and galantamine are three drugs with acetylcholinesterase (AChE)-inhibiting activity that are currently being used to treat patients suffering from Alzheimer's disease. We have studied the neuroprotective effects of these drugs, in comparison with nicotine, on cell death caused by ␤-amyloid (A␤) and okadaic acid, two models that are relevant to Alzheimer's pathology, in the human neuroblastoma cell line SH-SY5Y. Galantamine and donepezil showed a U-shaped neuroprotective curve against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
0
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(103 citation statements)
references
References 35 publications
9
85
0
9
Order By: Relevance
“…In experiments using rat cortical neurons, Takada et al (9) showed that the neuroprotection afforded by donepezil was prevented by methyllycaconitine (MLA), an α7-selective nAChR antagonist, but not by scopolamine, a muscarinic (m)AChR antagonist. These results were consistent with a previous study (31), which observed that the neuroprotective effect of donepezil was reversed by MLA in human neuroblastoma cells and that donepezil exerted neuroprotective effects via nAChRs. Conversely, Miki et al (12) reported that both mecamylamine, a nAChR antagonist, and scopolamine, were unable to affect the neuroprotective effect of donepezil on RGCs in vitro.…”
Section: Discussionsupporting
confidence: 83%
“…In experiments using rat cortical neurons, Takada et al (9) showed that the neuroprotection afforded by donepezil was prevented by methyllycaconitine (MLA), an α7-selective nAChR antagonist, but not by scopolamine, a muscarinic (m)AChR antagonist. These results were consistent with a previous study (31), which observed that the neuroprotective effect of donepezil was reversed by MLA in human neuroblastoma cells and that donepezil exerted neuroprotective effects via nAChRs. Conversely, Miki et al (12) reported that both mecamylamine, a nAChR antagonist, and scopolamine, were unable to affect the neuroprotective effect of donepezil on RGCs in vitro.…”
Section: Discussionsupporting
confidence: 83%
“…These data suggest a significant reduction in the levels of nAChRs α3, α7 and β2 protein subunits observed in cell lines exposed to peptide [37]. The progressive deterioration of the cholinergic system, together with the pharmacological evidence of AChEIs, have led to the development of cholinergic hypothesis, widely accepted and becomes evident by drugs such as donepezil, rivastigmine and galantamine, which act as AChEIs to increase the concentration of ACh between the synaptic cleft and modulate the nAChRs such as potent allosteric ligands [18].…”
Section: IImentioning
confidence: 99%
“…Galantamine commercialized under the generic name of Reminil® was the first alkaloid isolated from different species of Amaryllidaceae (Leucojum spp., Narcissus species, Galanthus spp) and is the most recently ACHEI approved in many countries for the symptomatic treatment of Alzheimer´s disease [51]. However, the pharmacological history of galantamine shows that it has been used throughout Eastern Europe since 1950, and the plant extracts with this kind of active compound were initially used to treat nerve pain and poliomyelitis [52].Galantamine is a cholinergic drug with antioxidant properties; neuroprotective and anti-apoptotic action [18,53] by its dual mechanism of action; moreover, it regulates the cholinergic transmission as ACHEI and allosterically modulates nAChRs [54]. The drug stimulates choline acetyltransferase activity and enhances the release of acetylcholine neurotransmitter, increasing its concentration in the synaptic clefts [53].…”
Section: Ad Treatment: Amaryllidaceae Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar neurotoxicity experiments were performed in primary cultures of bovine adrenal chromaffin cells (BCCs) that were prepared as described by Moro et al (1990) as well as in the tumoral cell line from human neuroblastoma SH-SY5Y that were prepared as previously described (Arias et al, 2005).…”
Section: 3-cell Culturesmentioning
confidence: 99%